2014
DOI: 10.1002/jat.3027
|View full text |Cite
|
Sign up to set email alerts
|

Parabens can enable hallmarks and characteristics of cancer in human breast epithelial cells: a review of the literature with reference to new exposure data and regulatory status

Abstract: A framework for understanding the complexity of cancer development was established by Hanahan and Weinberg in their definition of the hallmarks of cancer. In this review, we consider the evidence that parabens can enable development in human breast epithelial cells of four of six of the basic hallmarks, one of two of the emerging hallmarks and one of two of the enabling characteristics. In Hallmark 1, parabens have been measured as present in 99% of human breast tissue samples, possess oestrogenic activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 112 publications
1
78
0
2
Order By: Relevance
“…However, more and more studies have demonstrated that parabens are an emerging group of endocrine-disrupting chemicals, which may modulate or disrupt the endocrine system to affect the reproductive system, cause immune dysfunction, and produce developmental and behavioral disorders (Kang et al, 2013;Karpuzoglu et al, 2013;Meeker et al, 2011;Oishi, 2002;Piao et al, 2014;Soni et al, 2005). In addition, several studies have reported that parabens were associated with breast cancer etiology, and lead to a potential increase in breast cancer incidence (Darbre et al, 2004;Darbre and Harvey, 2014;Harvey, 2004). Moreover, conventional toxicity tests also show that parabens were toxic to aquatic organisms, such as algae, invertebrate and fish (Bazin et al, 2010;Dobbins et al, 2009;Yamamoto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, more and more studies have demonstrated that parabens are an emerging group of endocrine-disrupting chemicals, which may modulate or disrupt the endocrine system to affect the reproductive system, cause immune dysfunction, and produce developmental and behavioral disorders (Kang et al, 2013;Karpuzoglu et al, 2013;Meeker et al, 2011;Oishi, 2002;Piao et al, 2014;Soni et al, 2005). In addition, several studies have reported that parabens were associated with breast cancer etiology, and lead to a potential increase in breast cancer incidence (Darbre et al, 2004;Darbre and Harvey, 2014;Harvey, 2004). Moreover, conventional toxicity tests also show that parabens were toxic to aquatic organisms, such as algae, invertebrate and fish (Bazin et al, 2010;Dobbins et al, 2009;Yamamoto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Parabens also can inhibit the suppression of breast cancer cell growth by hydroxytamoxifen, and through binding to the oestrogen-related receptor gamma may prevent its deactivation by growth inhibitors. The authors concluded that there is evidence that parabens could have alleged responsibility in the occurrence of breast cancer (18).…”
Section: Discussionmentioning
confidence: 99%
“…Consumer products that contain constituents with endocrine-disrupting activity, such as parabens, are associated with increased breast cancer incidence in women Harvey and Darbre, 2004;Darbre and Charles, 2010;Darbre and Harvey, 2014). It was reported that unchanged parabens were present in human urine, and also tissues (Ye et al, 2006).…”
Section: Discussionmentioning
confidence: 99%